"Lies My Teacher [Educator] Still Tells": Using Critical Race Counternarratives to Disrupt Whiteness in Teacher Education. Issue 3 (2nd July 2020) - Aronson, Brittany; Meyers, Lateasha; Winn, Vanessa
Abstract: The purpose of this study was to disrupt whiteness through the use of critical race counternarratives during a critical literacy workshop with middle-school preservice teachers. Over two years, 57 preservice teachers participated in and reflected on their experiences reading master narratives and viewing counternarrative texts in a critical literacy workshop. Students responded in a variety of ways that ranged from displacing responsibility for their ignorance about the counternarrative texts onto educational structures, to troubling their roles in reproducing oppressive school environments and considering action steps for future teaching. Our research has important implications for preservice teachers, teacher educators, and those interested in implementing preservice teacher educator curriculum using a critical race theory lens.